2017
DOI: 10.1063/1.5002715
|View full text |Cite
|
Sign up to set email alerts
|

Line shape engineering of sharp Fano resonance in Al-based metal-dielectric multilayer structure

Abstract: Articles you may be interested in Thermochromic VO 2 thin films on ITO-coated glass substrates for broadband high absorption at infra-red frequencies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
(84 reference statements)
0
26
1
Order By: Relevance
“…S2(a) and S2(b) in the supplementary material indicate that the shape of the present Fano resonance is sensitive to Δκ DR1-PS and not sensitive to Δn DR1-PS . Furthermore, the position of the present Fano resonance is insensitive to both Δκ DR1-PS and Δn DR1-PS ; since the central position of the Fano resonance normally coincides with that of the sharp mode (PWG mode in the present sample), 25,26,42,43 it is not very much affected by the changes in the optical constants governing the broad mode (HLG mode). From these calculated results of ATR spectra, along with those of absorption spectra presented in Figs.…”
Section: E Mechanism Of Line Shape Modulation By Lightmentioning
confidence: 70%
See 2 more Smart Citations
“…S2(a) and S2(b) in the supplementary material indicate that the shape of the present Fano resonance is sensitive to Δκ DR1-PS and not sensitive to Δn DR1-PS . Furthermore, the position of the present Fano resonance is insensitive to both Δκ DR1-PS and Δn DR1-PS ; since the central position of the Fano resonance normally coincides with that of the sharp mode (PWG mode in the present sample), 25,26,42,43 it is not very much affected by the changes in the optical constants governing the broad mode (HLG mode). From these calculated results of ATR spectra, along with those of absorption spectra presented in Figs.…”
Section: E Mechanism Of Line Shape Modulation By Lightmentioning
confidence: 70%
“…[1][2][3]12,13 In recent years, we have pursued studies of the Fano resonance in simple multilayer structures both experimentally and theoretically. [18][19][20][21][22][23][24][25][26][27] The samples studied are metal-dielectric-dielectric (MDD) threelayer structures [18][19][20][21][22]25,27 and all-dielectric four-layer (DDDD) structures, 26 which are attached to a high-index prism to construct a Kretschmann attenuated-total-reflection (ATR) configuration. We demonstrated that in angle-scan ATR spectra of these samples, sharp Fano line shapes are generated and can be controlled easily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetry breaking in planar photonic crystals results in a well-known phenomenon of introducing sharp Fano resonances excitable by free-space illumination [31,[40][41][42][43][44][45][46]. There are two requirements for such a feature to be observed at normal incidence: (1) a mode must exist in the band diagram at the center ("Gamma point") of the First Brillouin Zone (FBZ) and (2) the mode must not be excluded by symmetry considerations.…”
Section: Symmetry Breaking In Planar Photonic Crystalsmentioning
confidence: 99%
“…The state of the art for SPR coupled PWG sensors is that there are several publications [22][23][24][25][26][27] proposing theoretical designs, but there are only some few reports of experimental results; experimental studies published at the present are based on plasmonic metals like Ag, Al, Au and one based on Ge-doped SiO 2 [15,[28][29][30]. In this paper we report, firstly, the experimental observation of SPPs in the Kretschmann configuration produced at a TiN/air interface.…”
Section: Introductionmentioning
confidence: 93%